A new shallow-marine, high-latitude record of the trace fossil Macaronichnus in Miocene, reworked delta-front clinoforms, Punta Basílica, Tierra Del Fuego, Argentina. Issue 4 (1st October 2020) - Olivero, Eduardo B.; López Cabrera, María I.
Abstract: A new high-latitude record of the trace fossil Macaronichnus segregatis degiberti is documented from the lower Miocene Punta Basílica beds, Tierra del Fuego, which were previously considered to be deep-marine channel and levee deposits. Based on a combined ichnological and sedimentological study, however, these beds are herein re-interpreted as shallow-marine, delta-front clinoform deposits. Macaronichnus -bearing beds in the stratigraphically older clinoforms are characterized by: (1) sandstones with wave ripples and wave-ripple cross-lamination; (2) cross-stratified sandstones forming large compound dunes and tidal bars; and (3) intervening heterolithic mudstone-sandstone couplets with current and wave ripples. The sedimentary facies preserving M. s. degiberti were deposited during the onset of transgression, indicated by wave and tide reworking of underlying steeply dipping, delta-front clinoforms deposits. The master bedding surfaces of compound tidal bars are characterized by a dense, monospecific fabric of M. s. degiberti . Compared with other Macaronichnus ichnofabrics, reported elsewhere as characterizing short colonization windows on foresets of tidal dunes or bars, the Punta Basílica ichnofabric represents a longer colonization window, associated with episodic reworking and redeposition of loose, nutrient-rich sand grains just above the master bedding surfaces. The record of M. s. degiberti in Tierra del Fuego supports the previous interpretations that restrain its producer to high-latitude, shallow-marine cold waters.